2000
DOI: 10.1046/j.1365-2672.2000.01067.x
|View full text |Cite
|
Sign up to set email alerts
|

The detection of astrovirus in sludge biosolids using an integrated cell culture nested PCR technique

Abstract: The work presented here demonstrates the utility of the integrated cell culture‐reverse transcriptase ‐polymerase chain reaction (ICC‐RT‐PCR) coupled with nested PCR to detect human astroviruses and enteroviruses in sludge biosolids. Viruses were concentrated by beef extract elution and organic flocculation prior to analysis by a plaque assay and ICC‐RT‐PCR. Astroviruses were detected in all but one sample and all of the samples were positive for enteroviruses. We have demonstrated the prevalence and frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…One methodological approach that has shown promising results is integrated cell culture strand-specific reverse transcription-PCR (ICC-RT-PCR) (Chapron et al 2000;Jiang et al 2004). However, this technique includes a culture-based step, and consequently it cannot be applied to NoV. Nuanualsuwan and Cliver (2002) reported that false-positive PCR signals could be eliminated by enzymatic treatment (ET) with proteinase K and RNase prior to nucleic acid extraction and RT-PCR.…”
Section: Introductionmentioning
confidence: 99%
“…One methodological approach that has shown promising results is integrated cell culture strand-specific reverse transcription-PCR (ICC-RT-PCR) (Chapron et al 2000;Jiang et al 2004). However, this technique includes a culture-based step, and consequently it cannot be applied to NoV. Nuanualsuwan and Cliver (2002) reported that false-positive PCR signals could be eliminated by enzymatic treatment (ET) with proteinase K and RNase prior to nucleic acid extraction and RT-PCR.…”
Section: Introductionmentioning
confidence: 99%
“…Also, only one or two types of enteric viruses were quantified in the previous studies; therefore, it is hard to determine and compare the prevalence of different types of enteric virus in biosolids, since the samples and sample processing methods varied from study to study. A few studies focused on the viral infectivity of biosolids, and the results showed that infectious astrovirus and enteroviruses were still present in the treated biosolids (9,18,42). However, no results on the occurrence of adenoviruses in biosolids have been reported.…”
mentioning
confidence: 99%
“…The occurrence of AstVs in water sources (9,29,31,40,51,60) and the occurrence of AstVs in sludge biosolids (10) have been reported, but the clinical significance and epidemiological impact of environmental AstV strains is unknown (60). Until recently, there have been no reports of antigenic or molecular characterization of environmental AstV isolates, but in a recent publication the authors described using restriction fragment length polymorphism (RFLP) to genotype such isolates (52).…”
mentioning
confidence: 99%